Factor analysis of dissociative personality disorder in Multimedia Communication Engineering students - Hernández Arroyo, Enrique Noé (Emerging Trends in Education, 2024)
The objective of this research is to identify a possible relationship between a pathological profile of dissociation in higher education students, with respect to the variables of consumption of addictive substances, violence in childhood, eating disorders, cognitive dysfunctions and work stress. The selected methodology is based on correlational quantitative analysis, under an ex post facto research design. The measurement instruments used are the Dissociative Experiences questionnaire (DES II), the Eating Disorders Inventory (EDI-3), the Addictions test (dast-10), the Mini-Mental (MMSE), the of Child Abuse (CTQ-SF) and the Work Stress Inventory (CPP). With the above, it is suggested that the group diagnosed with a dissociative personality disorder presents significant differences with respect to the five variables evaluated; Furthermore, for this group there is a prevalence with a high index on the stress scales, characterized by a form of compulsion and the presence of discomfort at an organic level. For the group evaluated with a non-dissociative personality profile, incipient cases of abuse, physical neglect and sexual abuse were identified. This condition requires correct channeling and rehabilitation due to its high progression in self-destructive behaviors.